A Geographic Information System Model for Educational Management for Higher in Thai Supply Chain - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The objectives of the research to develop and to assess a geographic information system model for Educational management for Higher Education institution in Thai Supply Chain. A sample groups were five experts in supply chain, five experts in geographic information system and five experts in Curriculum and Instruction. . All totalling fifteen experts. The research tool was questionnaire about a geographic information system model for Educational management for Higher Education institution in Thai Supply Chain . The findings reveal that a geographic information system model for Educational management for Higher Education institution in Thai Supply Chain is consisted of five key elements which are main elements suppliers university customers and consumer. The data analyzed by using arithmetic mean and standard deviation. The model assessment system using Back-Box technique. The overall evaluation result a geographic information system model for Educational management for Higher Education institution in Thai Supply Chain shows the overall rating mean of 3.64 and standard deviation of 0.61, suggesting that a geographic information system model for Educational management for Higher Education institution in Thai Supply Chain support sustainable geographic information system development.